2018
DOI: 10.3390/nu10081096
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Vitamin B12 is Better for Restoring a Low B12 Status Than a Daily High-Dose Vitamin Pill: An Experimental Study in Rats

Abstract: Vitamin B12 (B12) is present in foods of animal origin, and vegans are encouraged to take supplements with synthetic B12 in order to ensure a sufficient uptake. Recent rat studies suggest that natural (hydroxo-B12, HO-B12) and synthetic (cyano-B12, CN-B12) B12 behave differently in the body. Here, we test if a daily vitamin pill matches dietary B12 in ability to restore a low B12 status in rats. B12-depleted male Wistar rats (n = 60) were divided into five groups (n = 12 in each) and subjected to two weeks int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The saturable character of B12 uptake was also found in the intestine [ 21 ], though up- and downregulation of transporters was not demonstrated. A study in the rat model showed that several small doses of dietary B12 are more efficient in increasing blood and tissue B12, than a single large dose [ 11 ]. In a human study, Yajnik et al showed that supplementation with a physiological dose of oral B12 over 11-months in asymptomatic low B12 adolescent women significantly improved the B12 levels in these women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The saturable character of B12 uptake was also found in the intestine [ 21 ], though up- and downregulation of transporters was not demonstrated. A study in the rat model showed that several small doses of dietary B12 are more efficient in increasing blood and tissue B12, than a single large dose [ 11 ]. In a human study, Yajnik et al showed that supplementation with a physiological dose of oral B12 over 11-months in asymptomatic low B12 adolescent women significantly improved the B12 levels in these women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that CD320 knockout mice have B12 deficiency and have behavioural abnormalities, macrocytic anaemia, infertility and hypomethylation of DNA in the brain [ 8 ]. However, current knowledge on the absorption and tissue distribution of B12 has only been reported in few animal studies [ 9 , 10 , 11 , 12 , 13 , 14 ]. A study in Wistar rats showed that kidneys contained more B12 compared to other tissues such as lungs, spleen, brain, heart and liver [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of [ 57 Co]B12 in fetuses and maternal tissue were assessed by counting of the whole organs for 1 min in a gamma counter (2470 Wizard 2 Automatic Gamma Counter, Perkin Elmer, Skovlunde, Denmark) as described in [ 8 , 9 , 15 ]. In practice, the tissues were thawed on ice, cut into smaller pieces, and transferred to tubes for the gamma counter.…”
Section: Methodsmentioning
confidence: 99%
“…10 Vitamin B12 has several functions in methylation reactions in the body, acts as a cofactor in the form of methylcoblamin by the conversion of homocysteine to methionine and in the form of adenosylcobalamin in the transformation of methylmalonyl-CoA to succinyl-CoA. Both of these chemical reactions are important for cell division and growth, 11 Vitamin B12 plays a role in erythropoiesis and healthy neurological functions, 12 and it proved useful in the treatment of many diseases associated with inflammatory and oxidative stress. 13 The FDA have stated that cyanocobalamin is safe, there is no toxicity reported when cyanocobalamin given to animals, even at several thousand times their nutritional requirements.…”
Section: Introductionmentioning
confidence: 99%